Inclusive Mathematics Education Applied in Science through Assistive Technology: Advancing SDG 4 for Deaf Students in Indonesia - Siska Armeilia; Abna Hidayati; Jasrial; Ulfia Rahmi; Rayendra; Elsa Efrina; Eka Iswandy (Jurnal Penelitian Pendidikan IPA, 2026)
The integration of assistive technology is a key pillar in creating an inclusive mathematics education ecosystem for deaf students. This Systematic Literature Review (SLR) analyzed 49 reference sources to map the trends and effectiveness of learning media at secondary school levels. Findings show the primary focus on practical solutions utilizing students' visual cognitive strengths. Geometry is the most frequent topic (39%) due to its visualization nature that suits deaf visual learners. The reviewed literature indicates that integrating digital media—such as Augmented Reality (AR), Android applications, and subtitled videos—yields average validity scores ranging from 86.50%. This study concludes that transforming physical teaching aids into an interactive digital ecosystem is a crucial solution to bridge verbal communication barriers and mathematical abstraction in secondary schools.